Where is the client/patient voice in interprofessional healthcare team assessments? Findings from a one-day forum. Issue 1 (2nd January 2017) - Soklaridis, Sophie; Romano, Donna; Fung, Wai Lun Alan; Martimianakis, Maria Athina (Tina); Sargeant, Joan; Chambers, Jennifer; Wiljer, David; Silver, Ivan
ABSTRACT: There is a growing interest in interprofessional care (IPC) as a way to provide better healthcare. However, it is difficult to evaluate this mode of healthcare delivery because identifying the appropriate measurement tool is a challenge, given the wide diversity in team composition and settings. Adding to this complexity is a key gap in the IPC evaluation research: the client/patient perspective. This perspective has generally not been included in the development of IPC healthcare team evaluations. The authors received a Canadian Institute for Health Research Planning Grant to host a one-day forum with 24 participants from across Canada representing health professions such as social work, medicine, occupational therapy, and physical therapy, in addition to researchers, client/patient advocates, and hospital administrators. The overarching goal of the forum was to create a demonstration project that supports the development of an IPC assessment tool for healthcare teams that includes clients/patients. Using a concept mapping methodology, participants discussed client/patient inclusion in IPC assessments, and through a consensus process, chose a demonstration project for further development.